Effects of packaging and storage conditions on quality and storage life of tomato fruits (Lycopersicon esculentum MILL.) in Kura, Kano State, Nigeria - Dandago, M A; Ilesanmi, J O Y; Tamme, V (Journal of Postharvest Technology, 2017)
Nigeria being the second largest producer of tomatoes in Africa and 13th in the world has an estimated total postharvest loss of over 60%. This  prompted search for simple cost effective methods to extend the shelf life of tomatoes. This study carried out in Kura Kano state investigates  effects of packaging and storage conditions on quality and storage life of tomatoes. Green mature tomatoes were harvested early in the  morning, sorted, graded and divided into 3 kg lots each. Fruits were subjected to 3 postharvest dips, packaged in 3 packages and stored  under 3 conditions. Physico-chemical analyses were conducted on first day and there after every three days. Data generated were analyzed  using GLM procedure of SAS and means separated using LSD. Results of combined effects of packaging and storage showed that fruits  packaged in kraft paper bag and stored in zero energy cool chamber was the best combination because it maintained physico-chemical  parameters of the fruits within an acceptable limit up to 21 days of storage; it also maintained the fruit quality without the problem of chilling  injury which aggravates weight loss and rotting of fruits. This combination could therefore be recommended for short term storage of fresh  tomato fruits.
Keywords: Firmness; Loss; Postharvest; Paper; Tomato